Conceptual design and performance analysis of a biomimetic wind turbine inspired by the Dryobalanops aromatica seed / Chu Yung Jeh - Chu, Yung Jeh (2018)
A new 3-bladed downwind horizontal axis wind turbine (HAWT) inspired by mimicking the Dryobalanops aromatica seed is presented in this study. It was observed that the winged seed is able to align itself quickly against oncoming wind and subsequently descend slowly by autorotation due to its unique shape. Thus, the effect of mimicking the geometry of the winged seed in a HAWT design was investigated in this study. OpenFOAM®, an open source computational fluid dynamics (CFD) code, was used to predict the performances of the proposed biomimetic HAWT and a conventional twisted and tapered blade HAWT obtained from a research study conducted by Krogstad. The shape of the conventional HAWT blade sections was based on the National Renewable Energy Laboratory (NREL) S826 aerofoils. The MRFSimpleFOAM steady-state solver and the SST k-ω turbulence model were used to solve the fluid flow equations. All turbines have the same rotor diameter of 0.9 m simulated in mesh domain of size equal to 2 × 2 × 2 m3 with approximately 2 × 106 cell numbers under the same boundary conditions. The power coefficient, CP, thrust coefficient, CT, yaw and blade root bending stresses were predicted and discussed. The proposed biomimetic HAWT has CP = 0.386 and CT = 1.052 at optimum tip speed ratio (TSR) of 1.5 while the conventional HAWT has CP = 0.464 and CT = 0.974 at optimum TSR of 6.1 in free stream velocity, U∞ = 10 m/s. Although the power extraction capability is slightly lower, the biomimetic HAWT has starting torque 772 % higher than the conventional HAWT which means that it will have a better self-starting ability. The biomimetic HAWT is expected to function at low wind speed conditions due to its high solidity of 31.82 %. The preconed-blades feature of the biomimetic HAWT is able to reduce flapwise blade root bending stresses by utilising the centrifugal forces. The biomimetic HAWT has a higher yaw torque of 1.6 Nm compared with the conventional HAWT, 0.3 Nm and this indicated that the biomimetic HAWT has better yaw recovery. The aerodynamic performance of a reduced solidity biomimetic HAWT with the same solidity of 9.36 % as the conventional HAWT was predicted as well. The reduced solidity biomimetic HAWT has CP = 0.338 and CT = 0.988 at optimum TSR of 3.5 and it has lower aerodynamic performance compared with the original biomimetic HAWT. This implies that the sheet-like biomimetic HAWT blade sections are less efficient at low solidities. The mentioned sheet-like properties enable cheap fabrication methods for the proposed biomimetic HAWT blades such as metal stamping and vacuum forming. However, the biomimetic HAWT is expected to become structurally unstable when the wind shear within the rotor is high and thus it is not recommended for large-scale turbine farms. The biomimetic HAWT has the potential to be applied in water pumping, portable and domestic wind power systems. In conclusion, the biomimicry of Dryobalanops aromatica seed in turbine blade design shows interesting results and it is worthy of further investigation.